Modifikovaná Harringtonova operace v terapii rozsáhlých nádorových defektů acetabula - Lesenský, J; Blecha, O; Včelák, J (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2023)
PURPOSE OF THE STUDY The increasing prevalance of patients with metastatic bone cancer and their improved survival puts more emphasis on the quality of treatment of bone metastases. Although most pelvic lesions are treated non-operatively, extensive destruction of the acetabular segment poses a therapeutic challenge. A potential treatment option may be the modified Harrington procedure. MATERIAL AND METHODS At our department, this surgical procedure has been opted for in 14 patients (5 men and 9 women) since 2018. The mean age at the time of surgery was 59 years (range 42 to 73). Twelve patients suffered from metastatic cancer, one patient had a fibrosarcoma metastasis and one female patient presented with aggressive pseudotumor. Radiological and clinical followup of the patients was performed. Pain was assessed using the Visual Analogue Scale, and the Harris Hip Score and the MSTS score were used to evaluate the functional outcome. The paired samples Wilcoxon test was used to analyze the statistical significance of the difference. RESULTS The mean follow-up period was 25 months. At the time of assessment, ten patients were alive with the mean follow-up of 29 months (range 2 to 54 months) and four patients had died of cancer progression, with the mean follow-up being 16 months. No perioperative death or mechanical failure were reported. One female patient developed a hematogenous infection during febrile neutropenia, which was successfully managed with early revision and implant preservation. Statistically, a significant improvement in the MSTS (median 23) and HHS (median 86) functional scores compared to the preoperative values (MSTS median 2, p<0.01, r-effect size = 0.6; HHS preop median 0, p<0.005, r-effect size = -0.7) was observed. There was also a statistically significant reduction in pain (VAS postoperative median 1, VAS preoperative median 8, p<0.01, r-effect size = -0.6). All patients were capable of independent ambulation after the surgery, nine patients walked without support. DISCUSSION There are not many alternatives to this surgical procedure. Apart from non-operative palliative treatment, the options include ice cream cone prostheses or customized 3D implants which are, impractical in terms of time and cost. Our results are comparable to other studies, confirming the reproducibility and reliability of the method. CONCLUSIONS The Harrington procedure is an efective method for management of large acetabular tumor defects with good functional outcomes, an acceptable perioperative risk and a low risk of failure in the medium term, thus suitable also for patients with good cancer prognosis. Key words: umor, metastasis, acetabulum, pelvis, Harrington, reconstruction.
Keywords: dospělí; Plastic Surgery Procedures; Female; Bone Neoplasms; Adult; výsledek terapie; ženské pohlaví; Acetabulum; Reproducibility of Results; lidé; nádorová bolest; nádory kostí; Treatment Outcome; zákroky plastické chirurgie; acetabulum; retrospektivní studie; reprodukovatelnost výsledků; Male; Aged; lidé středního věku; senioři; mužské pohlaví; Cancer Pain; Retrospective Studies; Middle Aged; Humans